Nasotracheal Cavernous Hemangioma in Sheep (Case Report) - Farhang Sasani; Farhad Moosakhani; Mohsen Zafari; Diba Golchin; Zahra Moradi (International Journal of Veterinary Science and Research - Peertechz Publications, 2015)
A two-year-old ewe was presented to Veterinary Hospital, with a sudden onset of diarrhea, epistaxis, reluctance to move and recumbency which eventually led to its death. After necropsy and tissue sample collection for further examinations, histopathological study revealed large submucosal vascular structures with some thrombotic and blood filled spaces indicator of nasotracheal cavernous hemangioma, diffuse lymphocytic enteritis, hepatic diffuse mild vacuolar degeneration, severe pulmonary hyperemia and edema, cardiac and skeletal muscle sarcocystosis with severe hyperemia  and fragmentation of cardiac muscle fibers, mild perineuronal edema of the spinal cord, hyperemia and perineuronal (Purkinje cell) edema in the cerebellum, hyperemia with perineuronal and perivascular edema in the cerebrum, severe hyperemia with diffuse severe acute tubular necrosis, and mild intratubular and intrabowman's capsular space proteinaceous material in the kidney. To the authors' knowledge, this is the first case report of Nasotracheal hemangioma in sheep in Iran.